1998
DOI: 10.1159/000044933
|View full text |Cite
|
Sign up to set email alerts
|

Association of Apolipoprotein E Polymorphism with Lipoprotein Glomerulopathy

Abstract: Two cases of lipoprotein glomerulopathy with a new apolipoprotein E (Apo E) genotype, Ε3/Ε4, were diagnosed recently. These 2 cases, together with other cases documented in English literature made a total of 6 common isoforms of Apo E encountered in lipoprotein glomerulopathy. Although the calculated allele frequency of Ε2 is relative high in cases with lipoprotein glomerulopathy as compared with that in the general population (39.3 vs. 6.4–11.4%), the gradual emergence of Apo E isoforms other than E2/E3 in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In a study of 57 non-insulin-dependent Japanese diabetic patients, Horita et al [33]found an increased frequency of apo ε2 allele among patients with renal failure. In another recent report from Taiwan, Yang et al [34]found 2 new cases of lipoprotein glomerulopathy, both exhibiting apo E3/E4 genotype. In a European study, Boize et al [35]reported a twofold increase of nephropathy in E2 non-carriers with non-insulin-dependent diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 57 non-insulin-dependent Japanese diabetic patients, Horita et al [33]found an increased frequency of apo ε2 allele among patients with renal failure. In another recent report from Taiwan, Yang et al [34]found 2 new cases of lipoprotein glomerulopathy, both exhibiting apo E3/E4 genotype. In a European study, Boize et al [35]reported a twofold increase of nephropathy in E2 non-carriers with non-insulin-dependent diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…However, several new cases have recently been added to our file [9, 10, 11, 12, 13, 14]. To the best of our knowledge, 25 patients were reported from Japan, 1 from the United States [24], 2 from France [11, 25], 2 from Taiwan [12], and 2 from China [13, 14](fig. 5).…”
Section: Lipoprotein Glomerulopathymentioning
confidence: 99%
“…When the apo E phenotype was assayed by isoelectric focusing, most cases of LPG showed the heterozygous E2/3 or E2/4 [28], although a few were reported to have the wild-type E3/3 [25]or E2/2 that is found in familial type III hyperlipoproteinemia [33]. On the other hand, the apo E phenotype on a genetic basis (apo E genotype) determined by restriction fragment isotyping with Hha I was generally ε3/3 or ε3/4 [12, 15]. The discrepancy between the apo E phenotype and genotype indicates that the E2 isoform in LPG is not a product of the ordinary E2 gene in which codon 158 is different from that in the E3 gene [32].…”
Section: Apo E Variants and Polymorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…LPG recurs in transplanted kidneys (25)(26)(27), implicating systemic rather than renal factors in the development of the disease. Until now, a total of 34 cases of LPG have been reported, predominantly in Asians: 27 in Japanese (24,25,28 -33), 5 in Chinese (14,34,35), and 2 in French patients (36,37). At least 16 patients were heterozygous carriers of rare apoE variants.…”
Section: Discussionmentioning
confidence: 99%